Cultural Philosophy Review on The Cangget Agung Tradition of The Lampung Society - Shely Cathrin (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
This study aims to find the philosophical values in the Cangget tradition in Lampung Pepadun society based on an understanding of the importance of the Cangget tradition among Indonesian society in globalization era. To achieve this goal, the researcher conducted a literature review of several studies on Cangget and conducted interviews with several traditional leaders of Lampung Pepadun. The material object of the research is the Cangget tradition in Lampung Pepadun’s culture which is analyzed from the philosophy of culture as formal object. The results of the study indicate that the Cangget tradition is included in one of Lampung's cultures in the form of community social activities. This tradition has several meanings, among others, as a form of traditional celebration of the Lampung people, as well as a form of the efforts of the Lampung Pepadun’s people to maintain the purity of the traditions and customs. The Cangget tradition also has philosophical values, including the value of togetherness or social value, the value of unity, the value of honor, the value of democracy, and the economic value.